The Court of Rostyslav Mykhailovych, Prince and Dominus of Machou, in Hungary (An Excerpt from a Family History between the Late 13th and Mid 14th Centuries) - Voloshchuk, Myroslav (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
One of the least-explored aspects of the biography of the Ruthenian Prince Rostyslav Mykhailovych, a maternal nephew of King Daniel Romanovych of Rus’, is his court in a new homeland, the Kingdom of Hungary, between 1242/43 and 1262/64. It is known from various sources that he had numerous supporters among the secular and clerical nobility not only in Hungary but also in the lands of Galicia, Chernihiv, and Bolokhov. To date, however, too little information has been obtained from historical records containing clear mention of individuals who threw in their lot with the runaway prince in the lands of King Bela IV, especially after the defeat at Yaroslav on August 17, 1245. Having verified chronicles and Hungarian charters, the author concludes that the family of Rostyslav Mykhailovych and Princess Anna might well have been related to Lev and his sons, Fedir and Stephan, who were lords of Borod Land near Mukachevo in Bereg County. These people, who must have been descended from the nobility of Chernihiv or Galicia, succeeded one another in an effort to put Prince Rostyslav himself or his second cousin Iziaslav Volodymyrovych on the Galician throne throughout the 1240s and 1250s, all to no avail. What is important is that such attempts were always timed to coincide with the Mongol threat to the lands of the Romanids, which provided the claimants to the Galician throne with additional (albeit missed) chances of success. Their loyalty to the son-in-law of the Hungarian king was rewarded by the latter’s daughter Anna (terminus ante quem 1264); she granted them lands, which were afterwards in the successive possession of the last members of the Arpad dynasty on the Hungarian throne as well as the new kings from the Anjou dynasty. Borod Land remained in the family’s possession at least until the second half of the 14th century.